MIMESIS TIGA FASE EKSISTENSI KEHIDUPAN MANUSIA DALAM NOVEL SUNA NO ONNA KARYA ABE KOBO - Ahmad Iklil Saifulloh (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
The writer of this research is going to analyze the theory of the pioneer in Existentialism; Soren Kierkegaard’s the three phases of Human Existence (aesthetic phase, ethic phase and religious phase) This research indicates how the main characters Niki Jumpei at Suna No Onna novel are entrapped by society and nature. Their conditions are meaningless, powerless, nothingness and a sense of death. Yet, in the end, both of the protagonist characters recognize their meaning for their absurd life. By means using Descriptive Qualitative research, this research is focuses on describing the way of the main characters in Suna No Onna or Women in the Dunes provide the meaning of their life. Keywords: Three Phases of Human Existence, Suna No Onna, Abe Kobo